ANALISIS KINERJA TENAGA PELAKSANA GIZI PUSKESMAS DALAM PENANGGULANGAN BALITA GIZI BURUK DI KABUPATEN KEBUMEN - Sudikno .; Tetra Fajarwati; Rika Rachmawati; Irlina Raswanti; Sandjaja . (PERSATUAN AHLI GIZI INDONESIA, 2007)
WORK PERFORMANCE OF PUSKESMAS NUTRITION OFFICER IN THE MANAGEMENT OF SEVERE MALNUTRITION IN KEBUMENMinistry of Health published Guidelines for the Management of Severe Malnutrition in Puskesmas(Community Health Center) adopted from WHO book. It is a handbook for nutrition officer inPuskesmasto treat severe malnourished children in his areas. However, there has no study toevaluate work performance of nutrition officer in the implementation of the guidelines. A crosssectional study was conducted in the District of Kebumen, Central Java Province where severemalnourished children were high to determine work performance of Puskesmas nutrition officer.Samples of the study were 33 nutritition officers of Puskemas and 29 heads of Puskemas.Variables collected were characteristics of nutrition officer, budget and time allocated for nutrition,nutrition equipment and supplies, and management of severe malnutrition program; planning,implementation, monitoring, supervision, recording, reporting and evaluation constructed inquestionares. A composite of good and no good were based on variables to measure workperformance. The study team interviewed the samples by using questionaires. The sudy revealedthat 48.5 % nutrition officer had good working performance. Analysis showed that good workingperformance of nutrition officers in the management of severe malnutrition was associatedsignificantly with availability of nutrition equipment and supplies in Puskesmas and Posyandu(integrated health post) and intensive supervision from District Health Office.Keywords: severe malnutrition, work performance, nutrition officer